Greater Collagen‐Induced Platelet Aggregation Following Cyclooxygenase 1 Inhibition Predicts Incident Acute Coronary Syndromes. Issue 1 (25th July 2014) - Qayyum, Rehan; Becker, Diane M.; Yanek, Lisa R.; Faraday, Nauder; Vaidya, Dhananjay; Mathias, Rasika; Kral, Brian G.; Becker, Lewis C.
Abstract Greater ex vivo platelet aggregation to agonists may identify individuals at risk of acute coronary syndromes (ACS). However, increased aggregation to a specific agonist may be masked by inherent variability in other activation pathways. In this study, we inhibited the cyclooxygenase‐1 (COX1) pathway with 2‐week aspirin therapy and measured residual aggregation to collagen and ADP to determine whether increased aggregation in a non‐COX1 pathway is associated with incident ACS. We assessed ex vivo whole blood platelet aggregation in 1, 699 healthy individuals with a family history of early‐onset coronary artery disease followed for 6±1.2 years. Incident ACS events were observed in 22 subjects. Baseline aggregation was not associated with ACS. After COX1 pathway inhibition, collagen‐induced aggregation was significantly greater in participants with ACS compared with those without (29.0 vs. 23.6 ohms, p < 0.001). In Cox proportional hazards models, this association remained significant after adjusting for traditional cardiovascular risk factors (HR = 1.10, 95%CI = 1.06–1.15; p < 0.001). In contrast, ADP‐induced aggregation after COX1 inhibition was not associated with ACS. After COX1 pathway inhibition, subjects with greater collagen‐induced platelet aggregation demonstrated a significant excess risk of incident ACS. These data suggest that platelet activation related to collagen may play an important role in the risk of ACS.